Interactive Simulations of Biohybrid Systems - von Mammen, Sebastian Albrecht; Wagner, Daniel; Knote, Andreas; Taskin, Umut (Frontiers in Robotics and AI, 2017)
In this article we present approaches to interactive simulations of biohybrid systems. These simulations are comprised of two major computational components: (1) Agent-based developmental models that retrace organismal growth and unfolding of technical scaffoldings, and (2) interfaces to explore these models interactively. Simulations of biohybrid systems allow us to fast forward and experience their evolution over time based on our design decisions involving the choice, configuration and initial states of the deployed biological and robotic actors as well as their interplay with the environment. We briefly introduce the concept of swarm grammars, an agent-based extension of L-systems for retracing growth processes and structural artefacts. Next, we review an early augmented reality prototype for designing and projecting biohybrid system simulations into real space. In addition to models that retrace plant behaviours, we specify swarm grammar agents to braid structures in a self-organising manner. Based on this model, both robotic and plant-driven braiding processes can be experienced and explored in virtual worlds. We present an according user interface for use in virtual reality. We conclude this article with an outlook on future works on melding reality and virtuality to drive the design and deployment of biohybrid systems.